Induction mortality and resource utilization in children treated for acute myeloid leukemia at free‐standing pediatric hospitals in the United States. Issue 10 (21st February 2013) - Kavcic, Marko; Fisher, Brian T.; Li, Yimei; Seif, Alix E.; Torp, Kari; Walker, Dana M.; Huang, Yuan‐Shung; Lee, Grace E.; Tasian, Sarah K.; Vujkovic, Marijana; Bagatell, Rochelle; Aplenc, Richard
Abstract: BACKGROUND: Clinical trials in pediatric acute myeloid leukemia (AML) determine induction regimen standards. However, these studies lack the data necessary to evaluate mortality trends over time and differences in resource utilization between induction regimens. Moreover, these trials likely underreport the clinical toxicities experienced by patients. METHODS: The Pediatric Health Information System database was used to identify children treated for presumed de novo AML between 1999 and 2010. Induction mortality, risk factors for induction mortality, and resource utilization by induction regimen were estimated using standard frequentist statistics, logistic regression, and Poisson regression, respectively. RESULTS: A total of 1686 patients were identified with an overall induction case fatality rate of 5.4% that decreased from 9.8% in 2003 to 2.1% in 2009 ( P = .0023). The case fatality rate was 9.0% in the intensively timed DCTER (dexamethasone, cytarabine, thioguanine, etoposide, and rubidomycin [daunomycin]/idarubicin) induction and 3.8% for ADE (cytarabine, daunomycin, and etoposide) induction (adjusted odds ratio = 2.2, 95% confidence interval = 1.1‐4.5). Patients treated with intensively timed DCTER regimens had significantly greater antibiotic, red cell/platelet transfusion, analgesic, vasopressor, renal replacement therapy, and radiographic resource utilization than patients treated with ADE regimens. Resource utilization was substantially higher than reported in published pediatric AML clinical trials. CONCLUSIONS: Induction mortality for children with AML decreased significantly as ADE use increased. In addition to higher associated mortality, intensively timed DCTER regimens had a correspondingly higher use of health care resources. Using resource utilization data as a proxy for adverse events, adverse event rates reported on clinical trials substantially underestimated the clinical toxicities of all pediatric AML induction regimens. Cancer 2013. © 2013 American Cancer Society. Abstract : This study is the first comprehensive analysis of national trends in pediatric acute myeloid leukemia induction mortality and resource utilization. Using resource utilization data as a proxy for adverse events, adverse event rates reported on clinical trials substantially underestimated the clinical toxicities of all pediatric acute myeloid leukemia induction regimens.